Mapping the (Digital) Terrain. Issue 1 (2nd November 2021) - Anderson, Bradford A.; Dillon, Amanda
Abstract : This essay maps out some of the different ways in which the Bible intersects with digital culture, particularly in its written or textual dimensions. Four broad categories are used to give shape to the discussion: (1) the emergence and development of digital Bibles; (2) the use of digital biblical texts in religious services, liturgy, and other congregational contexts; (3) the intersection of biblical research and digital culture in academic scholarship; and (4) the iconic function of the digital biblical text in social and cultural contexts. What emerges is a picture of a diverse interrelationship between the Bible and digital culture, though not surprisingly, this is more evident in areas where there is a focus on the "text" rather than on material dimensions often associated with the sacred book.